2001
DOI: 10.1097/00005344-200108000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil Enhances Cardiac Endothelial Nitric Oxide Synthase Expression via Activation of Adenosine Triphosphate-Sensitive K Channel in Rat

Abstract: In the heart, nitric oxide activates an adenosine triphosphate (ATP)-sensitive K (K(ATP)) channel that is constructed of two subunits, i.e., an ATP-binding cassette protein sulfonylurea receptor (SUR2) and a pore-forming inward rectifier (Kir6.1 or 6.2). However, whether this K(ATP) channel affects nitric oxide activation is unknown. Our aim was to assess whether pharmacologic activation of the K(ATP) channel by nicorandil contributes to endothelial nitric oxide synthase (eNOS) levels. A total of 21 7-week old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…The dose of nicorandil was determined from our preliminary observations and the results of a previous study. 17 DS rats maintained on the 0.3% NaCl diet after 6 weeks of age served as age-matched controls (DS-C; nϭ8). The diet and tap water were provided ad libitum throughout the experiment.…”
Section: Animals and Experimental Protocolsmentioning
confidence: 99%
“…The dose of nicorandil was determined from our preliminary observations and the results of a previous study. 17 DS rats maintained on the 0.3% NaCl diet after 6 weeks of age served as age-matched controls (DS-C; nϭ8). The diet and tap water were provided ad libitum throughout the experiment.…”
Section: Animals and Experimental Protocolsmentioning
confidence: 99%
“…As mentioned previously, nicorandil contains a nitrate moiety in its chemical structure, allowing it to function as a NO donor. On the other hand, other investigations [56,57] showed that nicorandil is able to upregulate eNOS expression and increase NO release following ischemia. Thus, it seems that upregulation of eNOS, which leads to acute production of NO, in addition to the NO donor property of nicorandil and the nicotinamide moiety that makes it a potent hydroxyl radical scavenger, is partially or totally responsible for its beneficial effects in remission of IBD.…”
Section: Discussionmentioning
confidence: 94%
“…Findings of studies on cardiovascular disease have shown that nicorandil protects endothelial function (14) and enhances eNOS expression (16). In a monocrotaline-induced pulmonary arterial hypertension model, similar effects of nicorandil were identified (15).…”
Section: Discussionmentioning
confidence: 87%
“…A number of studies (14)(15)(16) have demonstrated the critical role of eNOS in PH, particularly in the maintenance of endothelial function. Findings of studies on cardiovascular disease have shown that nicorandil protects endothelial function (14) and enhances eNOS expression (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation